Review of the rove beetles (Coleoptera: Staphylinidae) from the Pliocene of Willershausen, Germany - Shaw, Josh Jenkins; Gehler, Alexander; Kaulfuss, Uwe (Zootaxa, 2024)
The rove beetle fauna (Coleoptera: Staphylinidae) (excluding the subfamily Silphinae) of the Pliocene of Willershausen (Lower Saxony, North Germany) is reviewed based on the type and other material of previously described or reported taxa, as well as two new specimens. Six subfamilies are represented in the deposit, with two subfamilial assignments considered tentative: Aleocharinae?, Micropeplinae, Oxytelinae, Paederinae, Staphylininae? and Tachyporinae. †Pliosyntomium Korge, 1967 syn. nov. is placed as a junior synonym of Paederus Fabricius, 1775. The following new combination is established: †Paederus schmidti (Korge, 1967) comb. nov. All rove beetle fossils from Willershausen housed in the Collections of the Geoscience Museum, University of Göttingen.